Clinico-Demographic Study of Chronic Renal Disease Patients Presenting with Congestive Cardiac Failure at a Tertiary Level of Hospital in Dhaka City - Biswas, Partha Protim; Amin, MM Ruhul; Huq, Md Ataul; Akter, Suraiya; Shamima, Mosammad Tanbir Nahar (Journal of Current and Advance Medical Research, 2022)
Background: Heart failure (HF) is a major public health issue, and it is associated with a high rate of mortality, morbidity, Objective: The purpose of the present study was to assess the demographic and clinical characteristics of the chronic renal disease patient with congestive cardiac failure (CCF). Methodology: This cross-sectional study was carried out in the Department of Medicine and Department of Cardiology in Dhaka Medical College Hospital, Dhaka, Bangladesh for six months after approval of the protocol on patients suffering from CCF. Study population was selected in the study group based on age more than 18 years of both sex and diagnosed case of CCF. Results: A total 100 patients were included and among them majority of the patients were aged between 51 to 60 years (32.0%). Among them 70.0% cases were male and 30.0% cases were female. About 58.0% cases were living in rural area and 46.0% cases of total subjects had a family income of 20,000-40,000 BDT. Co-morbidities of CCF patients of the study population showed that 53% had hypertension, 48% had ischemic heart disease, 34% had DM, 20.0% had dyslipidaemia, 16% had anaemia, 14.0% had asthma or COPD and rest 8% had history of atrial fibrillation. About 100.0% patients had shortness of breath along with 92.0% bilateral basal crepitation on auscultation; 80.0% had orthopnoea and 66.0% had raised JVP with 64.0% bilateral ankle edema. Conclusion: In conclusion males with hypertension and sedentary life style suffer from kidney diseases. Journal of Current and Advance Medical Research, January 2022;9(1):21-25